Translating planting and payoff in Edgar Wright’s Cornetto trilogy - Gupta, Taniya (Meta)

(untitled) (Les Presses de l’Université de Montréal, 2020)
“Planting and payoff” is a narrative technique in cinema where future plot events are foreshadowed by means of a verbal or visual hint that later acquires greater significance in hindsight. This article examines the use of this technique in British director Edgar Wright’s Cornetto trilogy (Shaun of the Dead, Hot Fuzz and The World’s End) in order to discover if these plants and payoffs are accessible to a Spanish speaking audience in the subtitled and dubbed DVD versions. Edgar Wright is known for his extensive use of verbal-visual foreshadowing and there are multiple Internet forums, film websites and vlogs by film students and fans that discuss the secrets waiting to be found by observant viewers. Using Chaume’s (2004a, 2012) list of signifying codes, this article attempts to isolate relevant frames of certain shots and, by breaking down the verbal and nonverbal information coded in each shot, it examines whether this foreshadowing is communicated in the subtitled and dubbed versions of these films. In doing so, it explores how information is shared between the different components of film language and the importance of taking into consideration the role of nonverbal codes in audiovisual translation.